FRI0196 NNC0109-0012 (anti-IL-20 MAB), well tolerated in healthy subjects and patients with rheumatoid arthritis. (23rd January 2014) - Al Kotbi, N.; Jensen, L.; Graff, L.B.
Abstract : Background: In patients with rheumatoid arthritis (RA), interleukin 20 (IL-20) is present in detectable amounts in synovial fluid, and IL-20 is thought to play a role in the pathophysiology of RA as a proinflammatory cytokine. NNC0109-0012 is a novel human monoclonal IgG4 antibody which binds to and neutralises IL-20. Currently, NNC0109-0012 is being developed for the treatment of patients with RA. Objectives: The primary objective of this phase 1 trial was to assess the safety and tolerability of single doses of NNC0109-0012 administered subcutaneously to healthy subjects (HS) and patients with RA. The secondary objectives were to assess the pharmacokinetics (PK), pharmacodynamics (PD) and immunogenicity. Methods: The trial was a single-centre, double-blind, placebo-controlled, single-dose, dose-escalation trial. Subjects, aged 18 to 75 years, were randomised 3:1. A total of 20 HS received one of the following 5 single doses of NNC0109-0012: 0.05, 0.2, 0.6, 1.5 or 3.0 mg/kg or placebo; 12 patients with RA received one of the following 3 single doses of NNC0109-0012: 0.05, 0.6 or 3.0 mg/kg or placebo. All doses were administered subcutaneously in the abdominal wall. Additional inclusion criteria for subjects with RA were: diagnosis of RA according to the American College of Rheumatology (ACR1987 classification) at least 3 months prior to randomisation with active disease characterised by a DAS28 >3.2, and on stable methotrexate treatment (≤25 mg/week) for at least 4 weeks and with concomitant folic acid intake of doses at 1 mg/day or 5 mg/week. Key safety parameters included adverse events (AEs), changes in vital signs, injection-site reactions, acute-phase cytokines, lymphocyte subsets and analysis of antibodies against NNC0109-0012. PK and PD markers (including CRP, ESR, RF and proteins biomarkers) were assessed. Results: A total of 93 AEs were reported for 24 of 32 (75%) subjects. Overall, there were equal proportions of subjects with an AE in the NNC0109-0012 and placebo groups (75%) and no difference in the proportion of AEs in HS and patients with RA receiving NNC0109-0012 (73% and 77% respectively). A total of 38 AEs were evaluated as probably/possibly related to trial product: NNC0109-0012: 28 events, 11 subjects (46%), placebo: 10 events, 5 subjects (63%). No deaths or AEs leading to withdrawal were reported. No subjects developed antibodies against NNC0109-0012 up to 106 days post-dosing. Linear PK in the dose range 0.05-3.00 mg/kg was indicated in both HS and patients with RA. No statistically significant difference was observed in the single-dose PK properties of NNC0109-0012 between HS and patients with RA. The mean terminal t1/2 ranged from 30–35 days in HS and from 25–28 days in patients with RA. No clinically relevant changes were observed in acute-phase cytokines, lymphocyte subsets, protein biomarkers, clinical laboratory parameters or vital signs. Conclusions: NNC0109-0012 appeared safe and well tolerated in HS and patients with active RA at single doses of 0.05–3.0 mg/kg. No antibodies against NNC0109-0012 were detected and linear PK was observed for NNC0109-0012. Disclosure of Interest: N. Al Kotbi: None Declared, L. Jensen Employee of: Novo Nordisk A/S, L. Graff Employee of: Novo Nordisk A/S at the time of trial conduct